How to choose a leader Machiavelli's advice to citizens - Viroli, Maurizio (Princeton University Press, 2016)
One of the greatest political advisers of all time, Niccolò Machiavelli thought long and hard about how citizens could identify great leaders--ones capable of defending and enhancing the liberty, honor, and prosperity of their countries. Drawing on the full range of the Florentine's writings, acclaimed Machiavelli biographer Maurizio Viroli gathers and interprets Machiavelli's timeless wisdom about choosing leaders.